Information security for optoelectronic ergatic system - Bushma, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
System representation in view of information security for otoelectronic ergatic
means is formed. Analytical description in the matrix form for corresponding systems is
received. Properties of the received bidimensional matrix are investigated.